Comparative Quality of Service Analysis of VPN Protocols on IPv6 - Sabela Trisiana Oktavia; Dimas Febriyan Priambodo; Nanang Trianto; Rahmat Purwoko (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2023)
The increase in internet users has led to the depletion of IPv4 supplies and the increase in cyber attacks, one of which is data leakage incidents. Several innovations were created such as switching to IPv6 which provides more addresses and implementing VPN technology to secure internet communications. The solution using VPN is believed to secure the network from various types of attacks from outside the network by creating a tunnel with a certain encryption algorithm as a data exchange path. Some studies reveal that using VPN can cause delay which will affect QoS performance. Therefore, this research will be conducted to provide evidence as well as a comparison between the WireGuard and L2TP / IPSec VPN protocols on IPv6 based on Quality of Service parameters which include delay, jitter, packet loss, throughput, and MOS with three tests namely iPerf3, FTP, and remote desktop . The measurement is done by making a sample model with mikrotik and 6to4 tunnel. From the series of tests, it is known that the L2TP/IPSec protocol is better than the WireGuard protocol judging by the performance generated in tests with FTP and remote desktop. This discovery can be used by end users or other researchers to use VPN more objectively based on the technology.